Theatrical practices and play models in working with children and youth in multicultural communities - Panayotova, Elena (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
ThÐµ article presents the experience, methodology and results achieved by the â€žArtists for Children and Youthâ€ program, existing for fourteen years between 2003 and 2017, comprising multicultural teams of 300 young artists from Europe, and 5000 children and youth from Bulgaria, Kenya and Tanzania. One innovative model for working with underprivileged children and youth through the means of the performing arts that emphasizes on the values in the arts and theatrical approaches as a bridge for communication, integration and fostering interpersonal and interethnic tolerance. The presented methodology combines five creative workshops: dance, music, puppet theater, mask theater in the system of the French pedagogue Lecoq, visual arts, and two training workshops in martial arts and yoga. The program content part offers a revival of oral traditions, a return to the forgotten ability of storytelling, handles and classifies tales from different cultures, provokes and develops the imagination. The practical experience presented adds valuable information to the potential that the theatre art brings to indirect learning and integration of the emotional experience of the individual.